Foehn jets over the Larsen C Ice Shelf, Antarctica. (19th June 2014) - Elvidge, Andrew D.; Renfrew, Ian A.; King, John C.; Orr, Andrew; Lachlan‐Cope, Tom A.; Weeks, Mark; Gray, Sue L.
Abstract : Previously unknown foehn jets have been identified to the east of the Antarctic Peninsula (AP) above the Larsen C Ice Shelf. These jets have major implications for the east coast of the AP, a region of rapid climatic warming and where two large sections of ice shelf have collapsed in recent years. During three foehn events across the AP, leeside warming and drying is seen in new aircraft observations and simulated well by the Met Office Unified Model (MetUM) at ∼1.5 km grid spacing. In case A, weak southwesterly flow and an elevated upwind inversion characterise a highly nonlinear flow regime with upwind flow blocking. In case C strong northwesterly winds characterise a relatively linear case with little upwind flow blocking. Case B resides somewhere between the two in flow regime linearity. The foehn jets – apparent in aircraft observations where available and MetUM simulations of all three cases – are mesoscale features (up to 60 km in width) originating from the mouths of leeside inlets. Through back trajectory analysis they are identified as a type of gap flow. In cases A and B the jets are distinct, being strongly accelerated relative to the background flow, and confined to low levels above the Larsen C Ice Shelf. They resemble the 'shallow foehn' of the Alps. Case C resembles a case of 'deep foehn', with the jets less distinct. The foehn jets are considerably cooler and moister relative to adjacent regions of calmer foehn air. This is due to a dampened foehn effect in the jet regions: in case A the jets have lower upwind source regions, and in the more linear case C there is less diabatic warming and precipitation along jet trajectories due to the reduced orographic uplift across the mountain passes.